A proteomics approach to decipher a sticky CHO situation. Issue 8 (25th May 2022) - Kumar, Swetha; Kumar, Amit; Huhn, Steven; DeVine, Lauren; Cole, Robert; Du, Zhimei; Betenbaugh, Michael
Abstract: Chinese hamster ovary (CHO) cells serve as protein therapeutics workhorses, so it is useful to understand what intrinsic properties make certain host cell lines and clones preferable for scale up and production of target proteins. In this study, two CHO host cell lines (H1, H2), and their respective clones were evaluated using comparative TMT‐proteomics. The clones obtained from host H1 showed increased productivity (6.8 times higher) in comparison to clones from host H2. Based on fold‐change analyses, we observed differential regulation in pathways including cell adhesion, aggregation, and cellular metabolism among others. In particular, the cellular adhesion pathway was downregulated in H1, in which podoplanin, an antiadhesion molecule, was upregulated the most in host H1 and associated clones. Phenotypically, these cells were less likely to aggregate and adhere to surfaces. In addition, enzymes involved in cellular metabolism such as isocitrate dehydrogenase (IDH) and mitochondrial‐d ‐lactate dehydrogenase ( d ‐LDHm) were also found to be differentially regulated. IDH plays a key role in TCA cycle and isocitrate‐alpha‐ketoglutarate cycle while d ‐LDHm aids in the elimination of toxic metabolite methylglyoxal, involved in protein degradation. These findings will enhance our efforts towards understanding why certain CHO cell lines exhibit enhanced performance and perhaps provide future cell engineering targets. Abstract : Applying proteomics tools to interpret the physiological causes of the sticky cell phenomena for Chinese Hamster Ovary cells in culture